2021
DOI: 10.1080/10463283.2020.1857082
|View full text |Cite
|
Sign up to set email alerts
|

Motivating voluntary compliance to behavioural restrictions: Self-determination theory–based checklist of principles for COVID-19 and other emergency communications

Abstract: An effective response to crises like the COVID-19 pandemic is dependent on the public voluntarily adhering to governmental rules and guidelines. How the guidelines are communicated can significantly affect whether people will experience a sense of self-initiation and volition, protecting compliance from eroding. From the perspective of Self-Determination Theory, a broad theory on human motivation and its interpersonal determinants, effective communication involves the delicate combination of providing rules an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
100
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(115 citation statements)
references
References 130 publications
13
100
0
2
Order By: Relevance
“…For example, authorities in the US are going to great lengths to encourage people who have chosen not to get vaccinated to change their minds. If people are experiencing need frustration (for example, because of vaccine passports), it is likely to be even more difficult to change their minds [ 17 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, authorities in the US are going to great lengths to encourage people who have chosen not to get vaccinated to change their minds. If people are experiencing need frustration (for example, because of vaccine passports), it is likely to be even more difficult to change their minds [ 17 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Satisfaction of these three psychological needs is critical for self-regulating and sustaining behaviours that improve health and well-being, such as exercising, smoking cessation and adherence to prescribed medications [ 14 , 15 ]. Recent evidence also suggests that the satisfaction of these needs is important for adherence to preventative COVID-19 measures [ 16 , 17 ]. In contrast, the frustration of these needs may elicit ill-being, a lack of motivation to act, or in some cases might even provoke defensiveness (doing the opposite of what is requested) [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…From a practical perspective, people receive ideally contextual support for their psychological needs from close others (e.g., family members and friends). At a macro-level, individuals' need-based experiences also depend to some extent upon governmental policy and, in particular, the government's capacity to systematically use a motivating communication style such that citizens more willingly endorse the measures (Martela et al, 2021), while also taking sufficiently risk-reducing measures to keep citizens' feelings of worry and insecurity under control.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…Such restrictions have varied between countries in the degree of coercion directed towards ordinary citizens, and it is unclear whether differences in the severity of measures have affected the spread of the pandemic; these circumstances have challenged thinking about public health actions on the individual, societal and governmental levels [1]. A recent rapid review of existing research on psychological aspects of Compliance with recommendations limiting COVID-19 contagion among university students in Sweden: associations with self-reported symptoms, mental health and academic self-efficacy pandemic-related quarantine indicated that negative long-term effects most often ensue, but that presenting a clear official rationale for restrictions that are voluntary, rather than mandatory, can mitigate the psychological distress associated with quarantine [2,3]. Awareness among public health authorities of known mental health challenges in relation to the pandemic has been signalled through recommendations on mental health, issued by the World Health Organization (WHO) [4] and by the Public Health Agency of Sweden (PHA) [5].…”
Section: Introductionmentioning
confidence: 99%